Sit-to-Stand (STS) Movement Analysis of the Center of Gravity for Human–Robot Interaction - Wang, Haiyan; Xu, Shanshan; Fu, Jiayu; Xu, Xiangrong; Wang, Zhixiong; Na, Ri Su (Frontiers in Neurorobotics, 2022)
With the development of China's aging process, the difficult problem of standing for the elderly (STS)has become the focus of attention of the elderly, families, and society. To solve the key difficulty is auxiliary stand robot and auxiliary stand for the development of technology and application, its foundation is whether from the perspective of health management and service is to find a suitable for the elderly to stand in the process of the center of gravity (COM) moving curve, but also full of the elderly to stand up in the process of psychological needs, such as comfort, pleasure, security method. To access the skeleton tracking technique used in this study, Vicon optical gait acquisition system, AMTI three-dimensional load success in getting a machine is suitable for the elderly to stand center of gravity (COM) of the process of moving curve, combined with the station process, speed and time sitting pose height analysis in the process of seeking to solve the old man to stand comfortably, pleasure, security, and so on psychological demand method. The application of this research result can provide theoretical and technical support for the later research and development of assisted standing robots and assist standing technology products so that the elderly can stand comfortably, happily, and safely. We will integrate medicine and industry, arts and science.